Pollution status of PAHs in the Malaysian aquatic environment for the past two decades - Tran, Duong; Kamara, Adams Alpha; Zakaria, Mohamad Pauzi (2012)
Global chemical pollution, especially contamination of PAHs have been widely investigated in recent years. These compounds have been of interest due to their toxicity, environmental persistence, high bioaccumulation in organisms and long-term adverse impacts on ecosystem as well as human health. Long-term exposure to these persistent organic pollutants in the environment or through the food chain may cause severe health implications. Major oil fields discovered in the East Coast of Peninsular Malaysia are producing crude oil that is been exported to other countries. Malaysia also occupies a strategic' location in the region as a major international shipping route for transporting crude oil from the Middle East to Northeast Asia. In addition to the rapid development during the last few decades in areas of industrialization, urbanization and motorization, Malaysia also have several potential sources of PAHs pollution, such as oil tankers and domestic oil production. The aquatic environment may be considered as the reservoir for PAHs generated in the environment. Apart from discharges from domestic, industrial and commercial effluents, aquatic environment also receives urban runoff loaded terrestrial contaminants, leaching from contaminated soil and airborne particles washed by rainfall. Therefore, the aquatic environment is a major focus for evaluating contamination by PAHs. This paper reviews earlier researches on PAHs in Malaysian aquatic environment in order to evaluate contamination status of these compounds for the last two decades. The result shows that level of PAHs increases for the last 20 years. Generally, the PAHs contamination level ranges from low to moderate in most of the aquatic environment of this region. Major cities such. as Terengganu, Kelantan, Penang; Johor, Negeri Sembilan and Selangor are hotspots of PAHs pollution. The paper suggests long-term monitoring to predict the status of PAHs pollution in the environment as it will be relevance for possible mitigation actions in the future.